2023
DOI: 10.1126/sciadv.adg6813
|View full text |Cite
|
Sign up to set email alerts
|

Progressive and instantaneous nature of lithium nucleation discovered by dynamic and operando imaging

Abstract: The understanding of lithium (Li) nucleation and growth is important to design better electrodes for high-performance batteries. However, the study of Li nucleation process is still limited because of the lack of imaging tools that can provide information of the entire dynamic process. We developed and used an operando reflection interference microscope (RIM) that enables real-time imaging and tracking the Li nucleation dynamics at a single nanoparticle level. This dynamic and operando imaging platform provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…[35,[39][40] In a recent work by Feng, et al the nucleation of Li on Cu (mimicking a Li anode-free battery) was observed in situ using a reflection interference microscope (RIM). [41] They identified a transition in nucleation mode from progressive to instantaneous as the SEI was formed. Initially, SEI formation reactions decreased Li nucleation rate, inducing progressive nucleation.…”
Section: Ruth Is a Materials Engineer And An Experienced Transmission...mentioning
confidence: 99%
See 2 more Smart Citations
“…[35,[39][40] In a recent work by Feng, et al the nucleation of Li on Cu (mimicking a Li anode-free battery) was observed in situ using a reflection interference microscope (RIM). [41] They identified a transition in nucleation mode from progressive to instantaneous as the SEI was formed. Initially, SEI formation reactions decreased Li nucleation rate, inducing progressive nucleation.…”
Section: Ruth Is a Materials Engineer And An Experienced Transmission...mentioning
confidence: 99%
“…This was attributed to the structure of the SEI on these areas, but the morphology of the Li, and therefore Li flux would also play a significant role. [41] The method developed by Feng, et al may be valuable for observing in situ nucleation and stripping of a range of metals and should be applied to other systems to confirm if the nucleation mode switching behaviour observed is common. Nucleation mechanisms can clearly impact the morphology of an electrodeposited metal and therefore dendrite formation.…”
Section: Ruth Is a Materials Engineer And An Experienced Transmission...mentioning
confidence: 99%
See 1 more Smart Citation
“…This voltage stabilization is a characteristic of the formation of an ion-conductive SEI layer at the electrified interface. 29 , 30 However, differences were evident in the nucleation overpotentials for the three systems. The Au/Cu system demonstrated the highest nucleation overpotential at −0.7865 V Li/Li + , suggesting a higher energy barrier for Li nucleation than the other systems.…”
mentioning
confidence: 98%